2019
DOI: 10.34172/ajcmi.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prevalence of blaSHV, blaTEM, and blaCTX Genes in Escherichia coli Isolated From Urinary Tract Infections

Abstract: BackgroundEscherichia coli is the most important agent of urinary tract infections (UTIs) which accounts for nearly 75% of the isolates (1, 2). Annually, about 150 million women suffer from UTIs worldwide (3). Uropathogenic E. coli (UPEC) strains often produce α-hemolysin which can cause an inflammatory response by the lysis of cells and the release of cytokine (4). β-lactamases are the enzymes that disrupt beta-lactam antibiotics and secret into the periplasmic space in gram-negative bacteria or out of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…The recent study reported that blaSHV from all E.coli isolates about 26.3% and ( 29.4%,27.27,20%) in all groups respectively , this is in agreement with a study conducted in Erbil City, Iraqi Kurdistan Region by (34),they reported the presence of blaSHV in about (28.5%) of E.coli isolates ; Another study supported our findings was done by (32) investigated that around 20.6% of E. coli isolates had blaSHV; Additionally, (35)revealed that the rate of blaSHV around 20% ; The rate of blaSHV in this study was higher than that reported by (36) in an Iranian hospital (5.5%) which were E. coli isolates.…”
Section: Discussionsupporting
confidence: 92%
“…The recent study reported that blaSHV from all E.coli isolates about 26.3% and ( 29.4%,27.27,20%) in all groups respectively , this is in agreement with a study conducted in Erbil City, Iraqi Kurdistan Region by (34),they reported the presence of blaSHV in about (28.5%) of E.coli isolates ; Another study supported our findings was done by (32) investigated that around 20.6% of E. coli isolates had blaSHV; Additionally, (35)revealed that the rate of blaSHV around 20% ; The rate of blaSHV in this study was higher than that reported by (36) in an Iranian hospital (5.5%) which were E. coli isolates.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, the highest presence of ESBLs was recorded for blaTEM and blaCTX-M, which was in line with earlier results [9,[31][32][33][34]. Although, some studies reported a lower rate of blaCTX-M, 28%, and 32%, respectively [35,36]. This discrepancy can be explained by different geography and the increase of genes transferring during the time.…”
Section: Discussionsupporting
confidence: 87%
“…Alipour and Jafari (35) showed that the uniplex PCR of the 45 ESBL-producing E. coli strains indicated that the bla TEM was the most abundant gene (89%) , followed by CTX-M (27%) and SHV (20%). These genes are common in Klebsiella pneumonia and E. coli (36).…”
Section: Discussionmentioning
confidence: 99%